(untitled) (Bangladesh Journal of Medicine, 2013)
Introduction: Acute kidney injury (AKI) is a common condition and its incidence is increasing . No study has been done so far on this subject in the Armed Forces. This retrospective study is therefore, to find out the incidence, etiology , predisposing factors, diagnostic approach, clinical course and finally outcome of the patients with AKI in this country, in a selected group of patients. Methods: This retrospective cross sectional study was conducted in Combined Military Hospital, Dhaka, from July 2007 to July 2011. Total 105 cases were included in this study. All were adult and their age of distribution was 18-80 years. Cases were studied in terms of etiology, mode of presentation, laboratory findings, management and response to treatment or outcome. Results: Mean age was 47.24+ 18.35 years. Male, female ratio was 3:2. Hypovolemia was the major (23.8%) etiological factor of AKI in this study due to acute gastroenteritis, 14.28% cases were due to different non-steroidal anti inflammatory drugs (NSAIDs), 9.52% cases due to rhabdomyolysis following physical assault and vigorous exercise, 7.61% cases were due to septicaemia, 8.57% cases were due to glomerulonephritis and 6.66% cases due to acute pyelonephritis.6.66% cases developed AKI due to falciparum malaria and 5.71% due to obstructive uropathy. Other causes of AKI in this study are contrast induced nephropathy 3.8%,postoperative AKI 4.76%,AKI due to vasculitis 3.8%,2.85% cases due to HELLP syndrome,0.95% case due to snake bite and 0.95% case due to thrombotic thrombocytopenic purpura(TTP). Oliguria (66.66%) and oedema (64.76%) were the commonest presentation in this study. Mean blood urea and serum creatinine level on admission being 9134 mg/dl and 4.292.55 mg/dl respectively. Haemodialysis was done in 44 cases, continuous renal replacement therapy (CRRT- continuous venovenous haemodialysis) was given in 6 patients, peritoneal dialysis in 5 patients and 49 cases were managed with conservative therapy alone. Complete recovery occurred in 88 patients, 8 had recovery with residual renal impairment, 6 patients developed end stage renal disease (ESRD) and 3 patients died due to septicaemia and multi-organ failure (MOF). Conclusion: Most of the cases of AKI are preventable if we can take due care of some common health problems like gastroenteritis and at the same time outcome can be rewarding if we can ensure early reporting, quick diagnosis and appropriate management DOI: http://dx.doi.org/10.3329/bjmed.v22i2.13587 Bangladesh J Medicine 2011; 22: 35-40